2004
DOI: 10.1088/0957-0233/15/10/007
|View full text |Cite
|
Sign up to set email alerts
|

Dual luminophor pressure-sensitive paint: III. Application to automotive model testing

Abstract: Porphyrins play key roles in natural energy conversion systems, including photosynthesis and oxygen transport. Because of their chemical stability, unique optical properties and synthetic versatility, porphyrins are well suited as chemical sensors. One successful application is the use of platinum porphyrin (PtP) in pressure-sensitive paint (PSP). Oxygen in the film quenches luminescence, and oxygen pressure was initially monitored by measuring the ratio of I(wind-off)/I(wind-on). But this ratio is compromised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 15 publications
0
46
0
Order By: Relevance
“…[6] They may also be used as pressure-sensitive paints (PSPs) [7,8] to image the total pressure of air (via oxygen pressure) on the surface of aircrafts and cars. [9,10] However, most sensors, regardless of whether optical or electrochemical, not only respond to the species of interest but also to temperature, whose effect therefore has to be compensated for, e.g., via a second (independent) measurement. We perceived that a sensor material that can yield independent information on the concentration of an analyte (such as oxygen) and on the actual temperature may provide an elegant solution to the above problem.…”
Section: Introductionmentioning
confidence: 99%
“…[6] They may also be used as pressure-sensitive paints (PSPs) [7,8] to image the total pressure of air (via oxygen pressure) on the surface of aircrafts and cars. [9,10] However, most sensors, regardless of whether optical or electrochemical, not only respond to the species of interest but also to temperature, whose effect therefore has to be compensated for, e.g., via a second (independent) measurement. We perceived that a sensor material that can yield independent information on the concentration of an analyte (such as oxygen) and on the actual temperature may provide an elegant solution to the above problem.…”
Section: Introductionmentioning
confidence: 99%
“…Principally, Pt II and Pd II porphyrins and porpholactones have been employed as probes for sensing barometric pressure, because their luminescence is strongly quenched by oxygen even in polymer solution. [20][21][22][23][24] Complexes of Eu III and Ru II have been presented for use in sensing T. [25,26] IridiumA C H T U N G T R E N N U N G (III) probes, in contrast, have not been widely investigated with respect to their suitability for sensing oxygen or barometric pressure [1,[27][28][29][30][31] and, until now, they have not been employed for the purposes of sensing T even though they display bright and tunable emission colors and phosphorescence lifetimes in the range 1-10 ms, [32][33][34][35] which makes them perfectly suited for lifetime imaging applications.…”
mentioning
confidence: 99%
“…The quenching of the photo-excited triplet state of Pt(II) complexes of porphyrins is the origin of their utility in pressure-sensitive paints (PSP) that allow for the continuous mapping of surface pressures [12][13][14][15][16]. We have found that the use of the fluorinated ligand T F PP in PSP formulations increases the phosphorescence lifetime of the paints and leads to photo-stable coatings, presumably because of the protection the pentafluorophenyl groups provide from singletoxygen-mediated oxidative degradation of the chromophore [13][14][15][16]. Further, T F PP was suggested as a chemically inert and strongly light-absorbing matrix in MALDI-TOF mass spectrometry [17].…”
mentioning
confidence: 99%